2016
DOI: 10.1111/jocn.13601
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver burden and prevalence of depression, anxiety and sleep disturbances in Alzheimer's disease caregivers in China

Abstract: To provide information about caregivers' current status while caring for patients with Alzheimer's disease and to understand caregiver burden and its related factors. Professionals who work with Alzheimer's disease should pay more attention to caregiver burden, especially those with mental and physical problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
4
10

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(189 citation statements)
references
References 58 publications
9
166
4
10
Order By: Relevance
“…Sleep disturbances increased such that nearly one-third of the families were facing this symptom at the third year of follow-up. We note that Liu et al 30 reported that sleep disturbances were a common physical problem for AD caregivers.…”
Section: Discussionmentioning
confidence: 71%
“…Sleep disturbances increased such that nearly one-third of the families were facing this symptom at the third year of follow-up. We note that Liu et al 30 reported that sleep disturbances were a common physical problem for AD caregivers.…”
Section: Discussionmentioning
confidence: 71%
“…Among the problems, psychological disorders suffered by caregivers include anxiety and depression. 18,19 The health they perceive is very low, and most report being dissatisfied or very dissatisfied with their health in general 20 affecting the quality of life 21 even in those caregivers who begin to take care of minor stages of the disease. 22 In addition, the psychological symptomatology is a crucial factor in the onset of discomfort and overload experienced by family caregivers of Alzheimer.…”
Section: Caregivers Of Patients With Alzheimer's Disease Suffer Greatermentioning
confidence: 99%
“…Among the problems, psychological disorders suffered by caregivers include anxiety and depression . The health they perceive is very low, and most report being dissatisfied or very dissatisfied with their health in general affecting the quality of life even in those caregivers who begin to take care of minor stages of the disease …”
Section: Introductionmentioning
confidence: 99%
“…These mental illnesses include anxiety [6-8], depression [6,9-15], poor sleep quality [7,8], and substance abuse or dependence [16]. Caregiving also affects the work force, with caregivers displaying greater absenteeism [6,7], higher rates of poor physical health [17-19], and higher mortality [20,21].…”
Section: Introductionmentioning
confidence: 99%